CIPROFLOXACIN RESISTANCE PATTERN AMONG BACTERIA ISOLATED FROM PATIENTS WITH COMMUNITY-ACQUIRED URINARY TRACT INFECTION - Ana Carolina Costa REIS; Susana Regia da Silva SANTOS; Siane Campos de SOUZA; Milena Góes SALDANHA; Thassila Nogueira PITANGA; Ricardo Riccio OLIVEIRA (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
SUMMARY Objective: To identify the main bacterial species associated with community-acquired urinary tract infection (UTI) and to assess the pattern of ciprofloxacin susceptibility among bacteria isolated from urine cultures. Methods: We conducted a retrospective study in all the patients with community-acquired UTI seen in Santa Helena Laboratory, Camaçari, Bahia, Brazil during five years (2010-2014). All individuals who had a positive urine culture result were included in this study. Results: A total of 1,641 individuals met the inclusion criteria. Despite the fact that participants were female, we observed a higher rate of resistance to ciprofloxacin in males. The most frequent pathogens identified in urine samples were Escherichia coli, Klebsiella pneumoniae and Staphylococcus saprophyticus. Antimicrobial resistance has been observed mainly for ampicillin, sulfamethoxazole + trimethoprim and ciprofloxacin. Moreover, E. coli has shown the highest rate of ciprofloxacin resistance, reaching 36% of ciprofloxacin resistant strains in 2014. Conclusion: The rate of bacterial resistance to ciprofloxacin observed in the studied population is much higher than expected, prompting the need for rational use of this antibiotic, especially in infections caused by E. coli. Prevention of bacterial resistance can be performed through control measures to limit the spread of resistant microorganisms and a rational use of antimicrobial policy.